2022
DOI: 10.3389/fnmol.2022.1038614
|View full text |Cite
|
Sign up to set email alerts
|

Synapse integrity and function: Dependence on protein synthesis and identification of potential failure points

Abstract: Synaptic integrity and function depend on myriad proteins - labile molecules with finite lifetimes that need to be continually replaced with freshly synthesized copies. Here we describe experiments designed to expose synaptic (and neuronal) properties and functions that are particularly sensitive to disruptions in protein supply, identify proteins lost early upon such disruptions, and uncover potential, yet currently underappreciated failure points. We report here that acute suppressions of protein synthesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 212 publications
0
3
0
Order By: Relevance
“…We (e.g. Minerbi et al, 2009; Hazan and Ziv, 2020) and others (Saalfrank et al, 2015) have found that under these conditions, neurons in culture are much more viable and resilient to insults such as pharmacological suppression of protein synthesis (Cohen et al, 2022). Indeed, in a separate set of experiments carried out on neurons maintained in small volumes in an incubator (i.e., without perfusion) and stained against Microtubule Associated Protein 2 (MAP2; somatodendritic compartments) and Neuro lament-heavy chain (axons), a shift toward a somatodendritic localization was observed, including aggregates within nuclei (Supp.…”
Section: Resultsmentioning
confidence: 93%
“…We (e.g. Minerbi et al, 2009; Hazan and Ziv, 2020) and others (Saalfrank et al, 2015) have found that under these conditions, neurons in culture are much more viable and resilient to insults such as pharmacological suppression of protein synthesis (Cohen et al, 2022). Indeed, in a separate set of experiments carried out on neurons maintained in small volumes in an incubator (i.e., without perfusion) and stained against Microtubule Associated Protein 2 (MAP2; somatodendritic compartments) and Neuro lament-heavy chain (axons), a shift toward a somatodendritic localization was observed, including aggregates within nuclei (Supp.…”
Section: Resultsmentioning
confidence: 93%
“…The structural integrity and functional properties of synapses further depend on continuous protein renewal, which in turn depends on the rate-limiting steps in protein synthesis [25]. Xu et al (2020) examined the eukaryotic translation initiation factor 4E (eIF4E) involved in the rate-limiting step in protein synthesis using a transgenic mouse model of ASD [14].…”
Section: Autism Spectrum Disordermentioning
confidence: 99%
“…A potential mechanism by which translational inhibitors might suppress neural signaling would be through mitochondrial poisoning (Cohen et al, 2022, p. 113; Scavuzzo et al, 2019, p. 50). In eukaryotic cells, mitochondrial function is dependent on nuclear‐derived proteins, despite independent protein synthesis in mitochondria themselves (Dudek, 2013, p. 115).…”
Section: Introductionmentioning
confidence: 99%